Photochemical reactivity of a lamellar lanthanum MOF. Issue 1 (13th November 2014) - Michaelides, Adonis; Aravia, Maria; Siskos, Michael G.; Skoulika, Stavroula
Abstract : The 2D lanthanum-dicarboxylate MOF [La2 (hex)3 (H2 O)6 ]·9H2 O (H2 hex = trans, trans -hexadiendioic acid) and some of its lower hydrates have been synthesized. Their photochemical rate constants show significant differences, attributed to the water structure within the hydrate. Abstract : A 2D lanthanum-dicarboxylate MOF of the formula [La2 (hex)3 (H2 O)6 ]·9H2 O (H2 hex = trans, trans -hexadiendioic acid or trans, trans -muconic acid) has been synthesized by the silica gel technique. The structure consists of metal–organic layers separated by a 2D network of water molecules. The metal–organic layers are made up of La 3+ arrays linked by the muconate ligands. Within a layer there is an infinite chain of short contacts between olefinic bonds allowing formation, upon UV irradiation, of three photoproducts. One of them was completely unexpected and its formation is explained by complex molecular movements in the solid state. The thermal instability of the MOF allowed isolation of five photochemically active lower hydrates. The rate constants of all hydrates were determined and show significant variations between them, attributable to structural rearrangements within the metal–organic layer brought about upon dehydration.